PENGUATAN KOMPETENSI TATA ARTISTIK MELALUI PELATIHAN MAKE UP DAN WARDROBE FILM FANTASI SISWA SMK NEGERI 8 SURAKARTA - Danissa Dyah Oktaviani; Sri Lestariningsih (AL HAZIQ: Journal of Community Service, 2025)
This community service activity aims to strengthen the artistic design competence of students in the Broadcasting and Film Study Program at SMK Negeri 8 Surakarta through training in make-up and wardrobe design for fantasy films. The background of this activity stems from the need to improve students’ abilities in the visual aesthetics of film production, particularly in the fantasy genre, which demands a high level of creativity in character design and costume arrangement. The implementation method consists of several stages, including planning, theoretical and practical training, production mentoring, and a final showcase in the form of a fantasy-themed fashion show. Participants were trained by professional practitioners in make-up artistry and costume design, using a hands-on approach that enabled students to apply artistic principles comprehensively. The results showed a significant improvement in technical skills, creativity, and collaboration among students during the production process. Moreover, the activity fostered appreciation for local cultural values, which were adapted into the fantasy costume designs. Thus, this training successfully served as a means of strengthening vocational competence relevant to the needs of the creative industry while supporting the development of the Profil Pelajar Pancasila through creative, independent, and collaborative character building.